2007
DOI: 10.1002/ajp.20369
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic influences on life‐history outcomes in free‐ranging male rhesus macaques

Abstract: Several studies have demonstrated that nonhuman primate males with low cerebrospinal fluid (CSF) levels of the serotonin metabolite 5-hydroxyindoleacetic acid (5-HIAA) exhibit antisocial behavior patterns. Included in these deleterious patterns are impulse control deficits associated with violence and premature death. No studies to date have longitudinally studied the long-term outcome of young subjects with low CSF 5-HIAA concentrations as they mature into adults. In this study we examined longitudinal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 42 publications
2
36
1
Order By: Relevance
“…In considering the clinical implications of our findings, it is important to note that, because MAO A enzymatic activity is responsible for the regulation of central serotonergic activity in terms of availability and subsequent extrasynaptic degradation (for a recent review, see Buckholtz and Meyer-Lindenberg, 2008), it would seemingly follow that having low MAO A activity will result in high serotonin levels. Indeed, MAO A knock-out mice have high circulating serotonin (Cases et al, 1995); however, when serotonin metabolites are examined in aggressive humans (Moffitt et al, 1998) as well as aggressive rhesus monkeys (Howell et al, 2007), they are found to be low. This difference is possibly attributable to compensatory mechanisms that primates may have developed to maintain control of high serotonin levels that could be neurotoxic (Baumgarten and Lachenmayer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In considering the clinical implications of our findings, it is important to note that, because MAO A enzymatic activity is responsible for the regulation of central serotonergic activity in terms of availability and subsequent extrasynaptic degradation (for a recent review, see Buckholtz and Meyer-Lindenberg, 2008), it would seemingly follow that having low MAO A activity will result in high serotonin levels. Indeed, MAO A knock-out mice have high circulating serotonin (Cases et al, 1995); however, when serotonin metabolites are examined in aggressive humans (Moffitt et al, 1998) as well as aggressive rhesus monkeys (Howell et al, 2007), they are found to be low. This difference is possibly attributable to compensatory mechanisms that primates may have developed to maintain control of high serotonin levels that could be neurotoxic (Baumgarten and Lachenmayer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Mehlman et al (1995) showed that the concentration in cerebrospinal fluid (CSF) of the serotonin metabolite 5-hydroxyindoleacetic acid (5-HIAA), which is consistent over time (Howell et al 2007), is negatively correlated to aggressiveness in the natal group and positively correlated with age at emigration from the natal group (see also §3). Thus, aggressive individuals disperse earlier than less aggressive ones prior to or during adolescence (note that this relationship is reversed for individuals that dispersed after the age of sexual maturity; Howell et al 2007).…”
Section: From Behavioural-dependent To Personality-dependent Dispersalmentioning
confidence: 99%
“…These results indicate the existence of an aggressive personality trait and suggest a strong role of personality in dispersal success and range expansion. In addition, in rhesus macaque males, social dominance rank in the new troop (after they emigrated to a new troop) was negatively correlated with juvenile CSF 5-HIAA concentrations, even if it has been shown that, males with low CSF 5-HIAA concentrations are less likely to be sought out as sexual partners by receptive females following emigration than are males with high CSF 5-HIAA concentrations (Howell et al 2007). …”
Section: From Behavioural-dependent To Personality-dependent Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of HVA have been related to aggressive behavior, wounding, sexual behavior, and social dominance in vervets and macaques (12,(20)(21)(22)(23). Numerous studies suggest associations between CSF MA metabolite concentrations and various human behavioral disorders (15,24,25), but other than relationships of CSF 5-HIAA to suicidal and aggressive behaviors (26), these associations remain mostly equivocal and nonreplicated, in part because of the difficulty in obtaining CSF from sufficient human subjects.…”
mentioning
confidence: 99%